Laser-Doping through Anodic Aluminium Oxide Layers for Silicon Solar Cells. (18th October 2015) - Lu, Pei Hsuan Doris; Lennon, Alison; Wenham, Stuart
Abstract : This paper demonstrates that silicon can be locally doped with aluminium to form localised p + surface regions by laser-doping through anodic aluminium oxide (AAO) layers formed on the silicon surface. The resulting p + regions can extend more than 10  μ m into the silicon and the electrically active p-type dopant concentration exceeds 10 20  cm −3 for the first 6-7  μ m of the formed p + region. Anodic aluminium oxide layers can be doped with other impurities, such as boron and phosphorus, by anodising in electrolytes containing the extrinsic impurities in ionic form. The ions become trapped in the formed anodic oxide during anodisation, therefore enabling the impurity to be introduced into the silicon, with aluminium, during laser-doping. This codoping process can be used to create very heavily doped surface layers which can reduce contact resistance on metallisation, whilst the deeper doping achieved by the intrinsic aluminium may act to shield the surface from minority carriers. laser-doping through AAO layers can be performed without introducing any voids in the silicon or fumes which may be harmful to human health.